2020
DOI: 10.1051/e3sconf/202017214010
|View full text |Cite
|
Sign up to set email alerts
|

Hygrothermal performance of paper plaster: influence of different types of paper and production methods on moisture buffering

Abstract: Paper as a material needs a lot of input energy. Many measures have been suggested to recycle paper, but still a huge amount of it ends in landfills. Hereby, one possibility for recycling paper - making paper plaster and putting it into service in indoor environment - is introduced. The study focuses on the moisture buffering properties of paper plaster. Two questions are under consideration in this article. Firstly, how paper type and production method influence the properties (dry density, drying shrinkage) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The moisture buffering value (MBV) has been studied by several authors [2], [3], [4], [5]. The results of earlier laboratory studies about the interior plaster made of waste paper have shown that the MBV of paper plaster is excellent (MBV>2.0 = "excellent") regardless of the type of paper [6], paper with clay [7], [8] or of the technology used to shred the paper [9].…”
Section: Introductionmentioning
confidence: 99%
“…The moisture buffering value (MBV) has been studied by several authors [2], [3], [4], [5]. The results of earlier laboratory studies about the interior plaster made of waste paper have shown that the MBV of paper plaster is excellent (MBV>2.0 = "excellent") regardless of the type of paper [6], paper with clay [7], [8] or of the technology used to shred the paper [9].…”
Section: Introductionmentioning
confidence: 99%